Cloud-Based Blockchain Security Framework for Ensuring Privacy in Wearable Health Devices - Shaharkar Bhushan Bharat (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Wearable health devices have transformed healthcare by providing real-time monitoring of patients’ vital signs. However, the continuous transmission of sensitive health data to cloud platforms presents significant security and privacy challenges. This paper proposes a Cloud-Based Blockchain Security Framework designed to protect health data while ensuring secure, seamless access for authorized users. By integrating lightweight cryptographic algorithms and blockchain technology, the framework guarantees tamper-proof data storage, robust user authentication, and enhanced data privacy. The system leverages smart contracts for automated access control and transaction logging. Extensive performance evaluation highlights significant improvements in authentication time and scalability, validating the framework’s potential for real-world healthcare applications.